Evidence for Mediated HCO(3)(−) Transport in Isolated Pea Mesophyll Protoplasts - Volokita, Micha (1981)
The kinetics of (14)C fixation, and inorganic C (C(inorg)) accumulation, have been followed in isolated pea mesophyll protoplasts. NaH(14)CO(3) was supplied to the protoplasts in media the pH of which was varied between 7 and 8. When (14)CO(2) fixation was plotted against the calculated concentration of free CO(2) in the media, the apparent K(m) for CO(2) was observed to rise as external pH increased. The V(max) did not alter significantly. Similarly, when C(inorg) uptake, either in the light or in the dark, was plotted against external CO(2) concentration the slope of the curves was steeper at higher external pH. Investigation of the time course of uptake showed that internal C(inorg) concentration rose throughout the experimental period, and that in the light it surpassed the external C(inorg) concentration after about 3 minutes. Irradiation of protoplasts previously taking up (14)C(inorg) in the dark brought about a sharp increase in the rate of (14)C(inorg) accumulation which was sustained for at least 20 minutes. Estimates of internal pH based on the distribution of labeled 5,5-dimethyloxazoladine-2,4-dione (DMO) between protoplast and medium suggested that internal pH altered relatively little with change in external pH. The values for internal pH as calculated from C(inorg) distribution were always higher than those calculated from DMO distribution, i.e. the internal C(inorg) concentration was higher than would be predicted on the assumption of passive distribution in accordance with pH. Addition of carbonic anhydrase to the external solution was without effect either on rate of (14)CO(2) fixation or C(inorg) accumulation. Various possible interpretations of the results are considered. It is concluded that the most reasonable explanation, consistent with all the data, is that HCO(3)(−) ions can cross the protoplast membranes, and that their passage is mediated by a transfer mechanism.